2015
DOI: 10.1007/s11524-014-9926-z
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Characteristics Differ Based on Use of Substances with Sex among an Urban Internet Sample of HIV-Discordant and HIV-Positive Male Couples

Abstract: Previous research with men who have sex with men (MSM) has found that substance use with sex is strongly associated with HIV acquisition and poor adherence to HIV treatments. Although some studies have assessed male couples' use of substances with unprotected anal sex, little is known on whether differences in their relationship dynamics are associated with their usage. Current HIV prevention initiatives underscore the importance of studying male couples' relationship dynamics. Using dyadic data from 28 HIV-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Additionally, being the older partner and reporting higher levels of internalized homophobia was associated with significantly lower reported binge drinking, while history of arrest, HIV-positive status and feelings of being more loved in a relationship was associated with binge drinking. These findings are in line with findings from other studies that have demonstrated significant effect of relationship-level factors on drug use and binge drinking in MSM couples (Martinez et al, 2016;Mitchell et al, 2015;Mitchell et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, being the older partner and reporting higher levels of internalized homophobia was associated with significantly lower reported binge drinking, while history of arrest, HIV-positive status and feelings of being more loved in a relationship was associated with binge drinking. These findings are in line with findings from other studies that have demonstrated significant effect of relationship-level factors on drug use and binge drinking in MSM couples (Martinez et al, 2016;Mitchell et al, 2015;Mitchell et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Substance use disparities also persist in the sexual and romantic endeavors in many SGM individuals. While some members of SGM communities use drugs and alcohol to enhance the pleasure of sexual encounters (Grov et al, 2013; Mitchell, 2015; Sugano et al, 2006), others, such as Black and Latino sexual minority men, have been reported doing so as a means of facilitating sexual comfort and exploration of one's sexual identity (Harawa et al, 2008; Mutchler et al, 2014). Use of substances during sexual encounters contributes to disparities in interpersonal violence (Bimbi et al, 2008; Kelly et al, 2011) and health concerns prevalent in SGM communities, including unsafe sex and the transmission of sexually transmitted infections (Greenwood and Gruskin, 2007; Lee et al, 2016).…”
Section: Discrimination and Social Normsmentioning
confidence: 99%
“…Although the current study sought to examine the linguistic underpinnings of perceived communication among gay couples as distal indicators of HIV behavioral health among couples, future studies should examine direct associations of language use and actual HIV preventive risk and behavior. These behavioral outcomes may include a variety of behaviors associated with perceived communication patterns, such as sexual risk behavior (Darbes et al, 2014), substance use during sex (Mitchell, 2015), as well as willingness to participate in CHTC (Mitchell, 2014b). Further, although the present analyses provide insight into the linguistic underpinnings of perceived communication associated with traditional HIV behavioral health outcomes among couples, it must be noted that the majority of these data were collected prior to the roll-out of pre-exposure prophylaxis (PrEP) in the summer of 2012 as an HIV prevention strategy (U.S. Food & Drug Administration, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Among partnered gay men, perceptions of these two communication patterns are associated with HIV risk behavior and preventive attitudes. For instance, among HIV-seroconcordant couples, high levels of perceived constructive communication reduce the odds of condomless anal sex with outside sex partners (Darbes et al, 2014) and are negatively associated with substance use during sex within the relationship (Mitchell, 2015). Relatedly, Mitchell (2014b) observed that among partnered gay men, although perceived constructive communication was positively associated, perceived avoidant communication was negatively associated with willingness to engage in couples HIV testing and counseling (CHTC; also referred to as couples voluntary counseling and testing), an evidence-based behavioral couples’ HIV intervention (Burton, Darbes, & Operario, 2010; El-Bassel et al, 2011) recently adapted for gay male couples in the United States (Sullivan et al, 2014).…”
mentioning
confidence: 99%
See 1 more Smart Citation